APLIKASI KITOSAN TERHADAP PERTUMBUHAN ANGGREK DENDROBIUM SONIA PADA TAHAP AKLIMATISASI - Raisah Bani; Parawita Dewanti; Didik Pudji Restanto; Laily Ilman Widuri; Firdha Narulita Alfian (Politeknik Negeri Lampung., 2022)
Dendrobium orchid is one of the ornamental plants with high economic value. Public interest in orchids, especially Dendrobium species is quite high and dominates the markets which make the seedling request also getting higher. The critical stage in determining the success of orchid seedling growth is also determined by acclimatization techniques. Differences in environmental conditions at the acclimatization stage can cause transpiration and interfere with nutrient absorption of plantlets. Chitosan as a natural organic material is a simple derivative of chitin which can function as a biofertilizer and bioimmuner. The purpose of this study was to determine the response of orchid seedling growth to the application of chitosan for the success of the acclimatization stage. The research method used a completely randomized design (CRD) with one factor, concentration of chitosan. The acclimatization stage using chitosan application with concentrations of 0 ppm, 2 ppm, 2.5 ppm, 3 ppm, 3.5 ppm, 4 ppm, 4.5 ppm and 5 ppm. The data obtained were then analyzed for variance with the F test at the 5% level. The treatment with significant effect was further tested with Duncan Multiple Range Test (DMRT) at 95% level. The results showed that the application of chitosan with a concentration of 3 ppm had a significant effect in increasing the parameters of plant growth percentage, plant height, number of leaves, leaf width, leaf length, root length, number of roots, and fresh weight of Dendrobium sonia orchid plants at the acclimatization stage.